1992
DOI: 10.1302/0301-620x.74b2.1544972
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of osteochondral fractures in rabbit knees. A comparison of Kirschner wires, fibrin sealant, and polydioxanone pins

Abstract: We compared fibrin sealant, polydioxanone (PDS) pins and Kirschner wires in the fixation of osteochondral fractures in rabbit knees. Standardised osteochondral fractures of the right medial femoral condyle were made in 56 adult New Zealand white rabbits. There were equal groups of control knees, and those which had Kirschner-wire, fibrin-sealant or PDS-pin fixation. No external immobilisation was used. One animal from each group was killed at two, three and four weeks. The remaining rabbits were killed at six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The excellent results published by Greve and Holste (1985), Claes et al (1986) and Plaga et al (1992), using PDS rods with inferior mechanical properties and no postoperative immobilisation, support this view. The initial enthusiasm for biodegradable implants in fracture fixation was tempered by early reports of foreign-body reactions.…”
Section: Discussionmentioning
confidence: 84%
“…The excellent results published by Greve and Holste (1985), Claes et al (1986) and Plaga et al (1992), using PDS rods with inferior mechanical properties and no postoperative immobilisation, support this view. The initial enthusiasm for biodegradable implants in fracture fixation was tempered by early reports of foreign-body reactions.…”
Section: Discussionmentioning
confidence: 84%
“…In order to eliminate the secondary surgery and resolve the shortcomings of permanent metallic wires, the fracture fixation with biodegradable wires made of polymeric materials was suggested and applied in the clinical trials [90,91]. The wires made of biodegradable synthetic polymers were applied in the fracture fixation of the knee [91], wrist [92], elbow [84] olecranon and patella [93] and small bones of hand [90] and their usage were compared with the metallic K-wires.…”
Section: Biodegradable Polymeric (Bp) Wiresmentioning
confidence: 99%
“…The wires made of biodegradable synthetic polymers were applied in the fracture fixation of the knee [91], wrist [92], elbow [84] olecranon and patella [93] and small bones of hand [90] and their usage were compared with the metallic K-wires. It was concluded that in both cases the healing time was the same and polymeric wires were suitable alternatives for the metallic ones [84,90,91,93]. Despite the high cost of polymeric biomaterials, the total expenses of treatment by polymeric wires was estimated lower than the metallic ones, since there is no need for the second surgery [93].…”
Section: Biodegradable Polymeric (Bp) Wiresmentioning
confidence: 99%
“…Vor teile der Fibrinkleberverwendung sind, dass der Knorpel nicht perforiert wird, die Bildung von GapJunctions reduziert wird und eine arthroskopische Applika tion möglich ist [19]. Fibrinkleber sollte nur bei kleinen Fragmenten oder additiv zu anderen Fixationstechniken eingesetzt werden [14].…”
Section: Therapiestrategienunclassified